Economic effects of digital logistics - Koroleva, Anna A. (Journal of the Belarusian State University. Economics, 2019)
Effects and economic effectiveness of digital transformation of logistics are investigated. The main directions of digital transformations in logistics are specified: electronic document management, pilotless transport, the Internet of things, 3D-printing. Effects of each of the directions are analyzed and also approaches to assessment of their cost efficiency are formulated. Examples of successful digital transformation of the logistic companies with assessment of their cost efficiency are given.
Keywords: logistics; digital transformation; IoT; drones; 3D printing; logistics efficiency